Linguistic Principles of Forming Linguistic Competence of Primary Class Students in The Process of Getting to Know the Features of The Text - Bazarova Ziyoda Eshbaevna (Researchparks Publishing, 2023)
In the article, great attention is paid to the multifaceted and complex process of developing all types of speech activity of elementary school students, as it is necessary for the integral formation of the personality, formation of values and worldview, establishing relationships with other people and learning the ability to interact, self–awareness and realization in various spheres of social activity largely depends on the fluency and mastery of the mother tongue. The study confirmed that the formation of speech competence of elementary school students is based on perception, multiplication, elementary analysis, composition and editing of statements of different styles and genres in oral and written forms. Therefore, the linguistic foundations of such activities in speech development classes are the main concepts and categories that primary school teachers should know. The author singles out the most effective of them in the formation of speech competence of elementary school students and gives a theoretical justification. They are: text, text informativeness, text theme, main idea, key words, text coherence and consistency, semantic and structural completeness, discreteness, text structure, text linearity and modality.